1977
DOI: 10.1007/bf00219993
|View full text |Cite
|
Sign up to set email alerts
|

On the yolk sac of the cat

Abstract: The phase of primitive erythropoiesis in the feline yolk sac lasts from the 14th to the 20th day after malting. The globular nucleated primitive erythroblasts are formed extravascularly to some extent, but they can be clearly distinguished from the endoderm. They do not undergo a denucleation and are still present in the circulating blood on the 45th day. Aging primitive erythroblasts are characterized by a loss of polysomes, by the appearance of long intracytoplasmic electron-lucent channels, and by a nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that macrophages occur in the yolk sac of animal and human embryos. The F4/80 + primitive macrophages appear in murine yolk sac at E9, and then differentiate into fetal macrophages [36], [37], [42], [43], [44]. Fetal liver begins to form its fundamental structure at E10, and primitive macrophages are detected in the hepatic sinusoid [36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that macrophages occur in the yolk sac of animal and human embryos. The F4/80 + primitive macrophages appear in murine yolk sac at E9, and then differentiate into fetal macrophages [36], [37], [42], [43], [44]. Fetal liver begins to form its fundamental structure at E10, and primitive macrophages are detected in the hepatic sinusoid [36].…”
Section: Discussionmentioning
confidence: 99%
“…Rhesus monkey ES cells have also been reported to give rise to EryP [53]. Similar patterns of EryP development were observed in these different mammalian species including formation in the YS, circulation as large, nucleated cells, loss of the nucleoli, and condensation of the nucleus [36, 172]. …”
Section: Primitive Erythropoiesis In Other Vertebratesmentioning
confidence: 88%
“…EryP have been observed in embryos from a number of different species including mouse, Syrian hamster [36, 140], Mongolian gerbil [171], rabbit, cat [172], merino sheep [173], pig, cow, and human (described in [132]). Rhesus monkey ES cells have also been reported to give rise to EryP [53].…”
Section: Primitive Erythropoiesis In Other Vertebratesmentioning
confidence: 99%